“A STUDY ON THE AWARENESS AND KNOWLEDGE ABOUT WEALTH MANAGEMENT IN THE COMMON MAN” (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Wealth management services have historically been reserved for the ultra-wealthy who require assistance with managing vast fortunes. Managing wealth is a skill and a science. Knowing the client inside and out is essential. However, the Internet has made financial management accessible to a much larger group of people, and one no longer needs a million dollars to take advantage of these services. A wealth manager's services extend beyond just stock and share management to include advising clients on the best collective funds to engage in. In addition, he can advise the investor on the best asset management strategy to pursue based on his or her unique circumstances. One can spend solely for the purpose of growing one's nest egg or strike a balance between long-term growth and short-term profits. A wealth manager's services may include providing impartial financial guidance on a wide variety of personal finance goods in addition to advising investors on the management of individual portfolios. In addition, he could aid in tax preparation, reducing expenses and obligations like capital gains tax. With their eyes on the breadth and direction of the markets, wealth managers can help their clients make swifterchanges to their financial portfolios, freeing up previously unrealized capital. To further assist their clients, some wealth managers offer web resources such as research tools, investment calculators, and access to wealth management reports. For wealthy investors, whether they be individuals or organizations, wealth management is all about maximizing returns while minimizing losses. A wealth manager needs extensive understanding of the financial markets, their instruments, participants, and the overall landscape.